SBAS APPROACH AND ITS COMPARISON WITH OTHER TYPES OF APPROACH (Perner's Contacts, 2016)
This paper discusses SBAS approach based on GNSS with aim to compare it with other systems. The first part addresses the basics of SBAS and approaches conducted using SBAS. The second part offers basic comparison of SBAS approach to APV Baro, ILS and GBAS.